Predisposing Factors and aetiologic diagnosis of eye’s Infection in Baghdad city/ Iraq - Munira Ch. Ismael; Elaf Sameer Mohameed (Zien Journals, 2022)
One of most common cause of ocular morbidity and blindness is microbial infections of the eye. There are numerous series that have been published of microbial eye’s infection from many parts of the world. The current research was detected the certain bacteria and fungus and predisposing variables which predisposed for the microbial eye’s infection. Annual study of the hospital record (194) cases were identified as microbial eye’s infection and treated at Ibn Al-Haytham Hospital for Ophthalmology from (June 2020 to May 2021). A review of predisposing variables, clinical and microbiological data were conducted sample, Professionals obtained the samples, which were subsequently subjected to testing microbial culture and biochemical tests. Results showed E. coli, Pseudomonas aeroginosa and S. epidermids were the most predominant species of bacteria at a higher proportion (53.52%) whereas P. mirabilis isolated to lower proportion (2.58%). The most prevalent risk factors were corneal trauma in (39.69%) and ocular surface disease in (25.25%) of cases.
Keywords: Predisposing Factors; eye infections; corneal trauma; P. aeroginosa